The shift from inpatient to outpatient hysterectomy for endometrial cancer in the United States: trends, enabling factors, cost, and safety. Issue 5 (16th March 2021) - Cappuccio, Serena; Li, Yanli; Song, Chao; Liu, Emeline; Glaser, Gretchen; Casarin, Jvan; Grassi, Tommaso; Butler, Kristina; Magtibay, Paul; Magrina, Javier F; Scambia, Giovanni; Mariani, Andrea; et al.
Abstract : Objective: To evaluate trends in outpatient versus inpatient hysterectomy for endometrial cancer and assess enabling factors, cost and safety. Methods: In this retrospective cohort study, patients aged 18 years or older who underwent hysterectomy for endometrial cancer between January 2008 and September 2015 were identified in the Premier Healthcare Database. The surgical approach for hysterectomy was classified as open/abdominal, vaginal, laparoscopic or robotic assisted. We described trends in surgical setting, perioperative costs and safety. The impact of patient, provider and hospital characteristics on outpatient migration was assessed using multivariate logistic regression. Results: We identified 41 246 patients who met inclusion criteria. During the time period studied, we observed a 41.3% shift from inpatient to outpatient hysterectomy (p<0.0001), an increase in robotic hysterectomy, and a decrease in abdominal hysterectomy. The robotic hysterectomy approach, more recent procedure (year), and mid-sized hospital were factors that enabled outpatient hysterectomies; while abdominal hysterectomy, older age, Medicare insurance, black ethnicity, higher number of comorbidities, and concomitant procedures were associated with an inpatient setting. The shift towards outpatient hysterectomy led to a 2500 savings per case during the study period, in parallel to the increased robotic hysterectomy rates (p<0.001). The post-discharge 30-day readmission and complications rate after outpatient hysterectomy remained stable at around 2%. Conclusions: A significant shift from inpatient to outpatient setting was observed for hysterectomies performed for endometrial cancer over time. Minimally invasive surgery, particularly the robotic approach, facilitated this migration, preserving clinical outcomes and leading to reduction in costs.